Identification of Benthic Foraminifera Presence in the Marginal Environments of Biliran Island, Philippines - Ernil D. Sumayao; Andrew S. Dy (Tropical Life Sciences Research, 2024)
Benthic foraminifera are unicellular marine micro-organism with a hard exoskeleton and commonly present in the benthic community of marine ecosystem. This study aimed to identify the benthic foraminifera present along the coastal areas of eight municipalities in Biliran Island, Philippines. Quadrat sampling was conducted and three samples per quadrant transect of 1 m × 1 m divided into nine squares were collected. The samples were then observed under the microscope, and the specimens seen were identified by comparing them with the images of the sample species from the website https://marinespecies.org/. The researchers conducted an in-situ collection of the foraminiferal shells from intertidal areas along shallow water coastlines of the island. Results showed that the coastal environment of Biliran Island has the presence of the genera Spirillina, Quinqueloculina, Marginopora and Sorites. The identified species were classified based on their feeding mechanisms as herbivory and passive suspension feeding. The presence of benthic foraminifera species along the coastal environments of Biliran Island provides a record of the environment where they are found, making them natural bioindicators of water quality. This study provides a baseline for further studies on the distribution and abundance of benthic foraminifera in the area and can contribute to the understanding of the environmental conditions of the coastal areas in Biliran Island.